Genome-Wide Identification and Characterization of Long Non-Coding RNAs in Longissimus dorsi Skeletal Muscle of Shandong Black Cattle and Luxi Cattle - Liu, Ruili; Han, Mingxuan; Liu, Xianxun; Yu, Kun; Bai, Xuejin; Dong, Yajuan (Frontiers in Genetics, 2022)
Background：There is increasing understanding of the possible regulatory role of long non-coding RNAs (LncRNA). Studies on livestock have mainly focused on the regulation of cell differentiation, fat synthesis, and embryonic development. However, there has been little study of skeletal muscle of domestic animals and the potential role of lncRNA. Results：RNA samples were collected from longissimus dorsi muscle samples of Shandong black cattle and Luxi cattle and libraries were constructed and sequenced. A total of 1415 transcripts (of which 480 were LncRNAs) were differentially expressed (q<0.05) in the different breeds, and fourteen of these RNAs were randomly selected and validated by qPCR. We found that the most differentially expressed LncRNAs were found on chromosome 9, with 1164 within 50 kb of a protein-coding gene. In addition, Pearson's correlation coefficients of co-expression levels indicated a potential trans regulatory relationship between the differentially expressed LncRNAs and 43844 mRNAs (r>0.9). The identified co-expressed mRNAs (MYORG, Dll1, EFNB2, SOX6, MYOCD, and MYLK3) are related to the formation of muscle structure, and enriched in muscle system process, strained muscle cell differentiation, muscle cell development, striated muscle tissue development, calcium signaling, and AMPK signaling. Additionally, we also found that some LncRNAs (LOC112444238, LOC101903367, LOC104975788, LOC112441863, LOC112449549, and LOC101907194) may interact with miRNAs related to cattle muscle growth and development. Based on this, we constructed a LncRNAs-miRNA-mRNA interaction network as the putative basis for biological regulation in cattle skeletal muscle. Interestingly, a candidate differential LncRNA (LOC104975788) and a protein-coding gene (Pax7) contain miR-133a binding sites and binding was confirmed by luciferase reporter assay. LOC104975788 may bind miR-133a competitively with Pax7, thus relieving the inhibitory effect of miR-133a on Pax7 to regulate skeletal muscle development. These results will provide the theoretical basis for further study of LncRNA regulation and activity in different cattle breeds. Conclusions：The data obtained in this study were used to predict muscle-related LncRNAs-miRNA-mRNA interaction networks, which can help elucidate the molecular mechanism of cattle muscle development. These results can be used to facilitate livestock breeding and improve livestock production.